X‐ray multiple diffraction of ZnO substrates and heteroepitaxial thin films. Issue 4 (27th January 2014) - Grundmann, Marius; Scheibe, Michael; Lorenz, Michael; Bläsing, Jürgen; Krost, Alois
<x xml:space="preserve">Abstract</x> We investigate Umweganregung reflections (X‐ray multiple reflections) for <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg5f9jbb9h" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />(HK.L)=(00.1)</alternatives>, (00.3), and (00.5) for a number of wurtzite structure ZnO samples, namely various bulk crystals (substrates), two ZnO thin films and a ZnO:Mg thin film, grown by pulsed laser deposition on a‐plane sapphire. Using a low divergence setup, we achieve a high angular resolution of 0.1<alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg5f9jbbb2" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />deg</alternatives> or better. We derive an analytical formula for peak positions as a function of wavelength <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg5f9jbbd5" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />λ</alternatives> and the lattice parameters a and c. The three investigated ZnO substrates exhibit all expected (kinematically allowed) reflections for Cu Kα1, Kα2, and Kβ. A lineshape analysis of the multiple reflection peaks shows that the width of certain reflections is determined by the spectral linewidth of the exciting copper lines. The thin films exhibit only slight broadening of the peaks but disappearance of several reflections. The a lattice constant can be determined from the azimuthal peak positions. Umweganregung scan for <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg5f9jbbfq" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />(HK.L)=(00.1)</alternatives> (<alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg5f9jbbg8" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />2θ=17.02deg</alternatives>) of a hydrothermally grown ZnO substrate, excited with Cu Kα1 radiation. The pattern is symmetric with respect to zero angle representing the (10.0) azimuth. <inline-graphic xlink:href="ark:/27927/pgg5f9jc27r" content-type="pssb201350297-gra-0001" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />